DAYA DUKUNG WADUK PLTA KOTO PANJANG KAMPAR PROVINSI RIAU - Siagian, Madju (Fakultas Perikanan dan Kelautan Universitas Riau, 2010)
A study on carrying capacity in the reservoir of Koto Panjang Hydro-electricPower Plant, Kampar, Riau Province, was conducted on May-October 2009. The studyaims to assess the quality and carrying capacity of the reservoir for the development offloating net cages (FNC) units that can be sustainably implementd. Carrying capacity ofthe reservoir was estimated based on P total and dissolved oxygen availability in thewater, while number of FNC was estimated based on the total P availability against thebiomass of fish in the FNC. Based on its carrying capacity, the number of FNC unitswhich can be exposed in the reservoir during the period of the study is 19,599 – 33,515.units. The existing utilization level for 900 FNC is actually about 2.7-4.6 % of thecapacity. This indicates that FNC is potential to be develoved. Regarding the potency ofpollution from Kampar and Batang Mangat river basin (allochtonous sources) and fromthe existing FNC (autochtonous sources) as well as regression analysis of total P contents,it is precdicted that the carrying capacity of the reservoir will considerably decreaseTherefore, it is recommended that number of FNC to be operated in Koto Panjangreservoir should be gradually reduced approximately to 1.32 % a year, up to a minimumnumber of 19,599 units, especially in the potential utilization zone of the reservoir.